Exposing Larvae to Night Lighting Inhibits Embryonic Diapause in the Next Generation in the Domestic Silkworm, Bombyx mori - Iwamoto, A.; Egi, Y.; Sakamoto, K. (Journal of Scientific Research, 2024)
The domestic silkworm (Bombyx mori) is reared under controlled environments. Therefore, silkworms may be exposed at night to light used by humans working or living nearby. Artificial light at night (LAN) disturbs natural lighting cycles and negatively affects insect physiology, behavior, and ecology in the field. However, the effects of dim LAN on domestic silkworms have not been assessed in detail. The present study investigated the effects of night lighting on diapause regulation in Bombyx mori, with a focus on light sensitivity. The silkworm larvae were exposed to LAN at intensity varying from 0.1‒100 lux under a short-day photoperiod that should induce diapauses, and then the incidence of diapause in eggs laid by resultant moths was evaluated. The incidence of diapause was 100 % in control (without night lighting) silkworms, but the incidence in those exposed to LAN ≥ 0.1 lux was < 2 %. These results showed that exposing larvae to night lighting at 0.1 lux under a short-day photoperiod substantially inhibited diapause induction in the next generation.